Pembaruan Islam Bidang Keluarga dan Relevansinya dengan Pelarangan Terhadap Penyimpangan Seksual: Islamic Family Reform and its Relevance to the Prohibition of Sexual Deviations - Suud Sarim Karimullah; Arif Sugitanata; Fawwaz Elmurtadho (ISTIDLAL, 2023)
Sexual deviations caused by the urge of lust that cannot be adequately controlled and the lack of understanding of religious teachings make humans no different from the actions carried out by animals. This research aims to see the prohibition of sexual perversion in Islamic teachings to maintain the sanctity of human nature. While this research is qualitative, with data collection done through literature studies, the data collected from these sources are analysed descriptively analytically with a historical dimension. The results of this study state that Islamic reform in the family field regulates the distribution of biological needs through marriage because Islam recognises that humans have a huge desire to have sex. In addition, Islam also prohibits various sexual deviations because it is a terrible act and far from human nature, so there are also legal sanctions for the perpetrators. Punishment for perpetrators of sexual perversion is intended to warn humanity and minimise actions that harm oneself or others.